A non-invasive reference-based method for imaging the cerebral metabolic rate of oxygen by PET/MR: theory and error analysis. (4th March 2021) - Narciso, Lucas; Ssali, Tracy; Iida, Hidehiro; St Lawrence, Keith
Abstract: Positron emission tomography (PET) remains the gold standard for quantitative imaging of the cerebral metabolic rate of oxygen (CMRO2 ); however, it is an invasive and complex procedure that requires accounting for recirculating [ 15 O]H2 O (RW) and the cerebral blood volume (CBV). This study presents a non-invasive reference-based technique for imaging CMRO2 that was developed for PET/magnetic resonance imaging (MRI) with the goal of simplifying the PET procedure while maintaining its ability to quantify metabolism. The approach is to use whole-brain (WB) measurements of oxygen extraction fraction (OEF) and cerebral blood flow (CBF) to calibrate [ 15 O]O2 -PET data, thereby avoiding the need for invasive arterial sampling. Here we present the theoretical framework, along with error analyses, sensitivity to PET noise and inaccuracies in input parameters, and initial assessment on PET data acquired from healthy participants. Simulations showed that neglecting RW and CBV corrections caused errors in CMRO2 of less than ±10% for changes in regional OEF of ±25%. These predictions were supported by applying the reference-based approach to PET data, which resulted in remarkably similar CMRO2 images to those generated by analyzing the same data using a modeling approach that incorporated the arterial input functions and corrected for CBV contributions. Significant correlations were observed between regional CMRO2 values from the two techniques (slope = 1.00 ± 0.04, R 2 > 0.98) with no significant differences found for integration times of 3 and 5 min. In summary, results demonstrate the feasibility of producing quantitative CMRO2 images by PET/MRI without the need for invasive blood sampling.